2014
DOI: 10.1021/ac5022198
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microfluidic Platform for Human Plasma Protein Depletion

Abstract: Many important biomarkers for disease diagnosis are present at low concentrations in human serum. These biomarkers are masked in proteomic analysis by highly abundant proteins such as human serum albumin (HSA) and immunoglobulins (IgGs) which account for up to 80% of the total protein content of serum. Traditional depletion methods using macro-scale LC-columns for highly abundant proteins involve slow separations which impart considerable dilution to the samples. Furthermore, most techniques lack the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 67 publications
(136 reference statements)
0
35
0
Order By: Relevance
“…blood), which are rich in highly abundant proteins (HAPs), such as immunoglobulins. Recently, Mei et al [74] reported a method of protein depletion integrated in an EWOD-DMF set up. The method relies on magnetic particles coated with specific antibodies or proteins towards HAPs which were brought into contact with the sample solution.…”
Section: Sample Preparation On Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…blood), which are rich in highly abundant proteins (HAPs), such as immunoglobulins. Recently, Mei et al [74] reported a method of protein depletion integrated in an EWOD-DMF set up. The method relies on magnetic particles coated with specific antibodies or proteins towards HAPs which were brought into contact with the sample solution.…”
Section: Sample Preparation On Chipmentioning
confidence: 99%
“…The group of Wheeler also integrated all necessary instrumentation in a benchtop device (18 Â 23 Â 30 cm), [57,74] (Fig. 11C).…”
Section: Integrated Dmf Platformsmentioning
confidence: 99%
“…Although there is a rising tendency to automate analytical procedures used in proteomic research through flow methodologies [10,[16][17][18][19], usually LAC is carried out in batch conditions (using the commercial columns and kits) [20] or using sophisticated chromatographic equipments [21][22][23], which implies a long procedure time and high consumption of consumables, or capability of laboratories to purchase expensive apparatus. If the LAC procedure is performed under flow conditions, this allows automation of the process, especially important when several samples need to be run, and reduces solution and sample manipulation steps and resultant losses, ex-vivo proteolysis or chemical modifications during procedures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive and comprehensive analysis of ferrofluidic manipulation on DMF devices has been previously reported therefore here we concentrate on aqueous droplets containing paramagnetic particles only [24,30,31]. Commercial "magnetic particles" for this purpose are based on (super)paramagnetic particles, where an iron oxide core is surrounded by a layer of silica, which can be functionalized as desired for a given application [32][33][34][35]. Many devices using magnetic actuation have been reported, and complex droplet movement has been demonstrated in three dimensions, including actuation of an inverted droplet [20].…”
Section: Introductionmentioning
confidence: 99%